Perceived stress and coping strategies among elderly people residing in geriatric centers of Nepal - Kharel, Sunita; Mandal, Gayananda; Parajuli, Pushpa; Mehta, Ram Sharan; Acharya, Baikuntha; Khapung, Anju (Journal of Psychiatrists’ Association of Nepal, 2024)
Introduction: Senior citizens are one of the most vulnerable groups in Nepalese society. Loneliness and stress among senior people are on the rise due to a lack of dependable caregivers and unmet medical and emotional needs. However, some elders may have better coping strategies based on their life experiences and physical/mental well-being. The objective of our study was to assess the stress and coping strategies among elderly people residing in government and private geriatric centers in Central Nepal. Materials and methods: A descriptive cross-sectional study was conducted among the 54 respondents selected conveniently from two geriatric centers in Devghat, Nepal. The centers were Devghat Samaj Kalyan Kendra, a government geriatric center, and Devghat NRNA Briddashram, a private geriatric center. Results: Results show that 51.9% of the seniors living in the facilities had moderate levels of stress while 1.8% of respondents reported high levels of stress. The most commonly used coping strategies included self-distraction followed by the use of positive reframing and religion. Among the elders living in government and private geriatric centers, a significant difference was observed in behavioral disengagement (p-value 0.003). However, no significant correlation was seen between the perceived stress scale score and overall coping score (p-value 0.08) among the respondents. Conclusion: Our study suggests that respondents in private geriatric center display more stress than the respondents in government geriatric center.